Bacterial Urinary Tract Infections Associated with Transitional Cell Carcinoma in Dogs. (1st May 2015) - Budreckis, D.M.; Byrne, B.A.; Pollard, R.E.; Rebhun, R.B.; Rodriguez, C.O.; Skorupski, K.A.
<x xml:space="preserve">Abstract</x> Background Urinary tract infections (UTI) are believed to be common in dogs with transitional cell carcinoma (TCC), but incidence and contributing factors have not been reported. Objectives To determine the frequency and bacterial agents associated with UTI in dogs with TCC and define contributing factors. Animals Eighty‐five dogs with a history of urogenital TCC undergoing treatment with chemotherapy that had at least 1 urine culture performed. Methods Medical records and culture results were retrospectively reviewed and ultrasound images were reviewed when available. Clinical factors were evaluated statistically for association with positive culture. Results Fifty‐five percent (47/85) of dogs had at least 1 positive culture during the course of treatment. Female dogs (80%, 40/50) were more likely than male dogs (29%, 10/35) to have at least 1 positive culture. Ultrasound examination determined that female dogs were more likely to have urethral (74%, 31/42) or trigonal tumor involvement (71%, 30/42) compared to male dogs (32%, 9/28 and 43%, 12/28, respectively). The most commonly isolated organisms were Staphylococcus spp. (23.9%, 29/121) and Escherichia coli (19.8%, 24/121). Dogs with urethral involvement of TCC were significantly more likely to have at least 1 positive culture than dogs without urethral involvement (75%, 30/40 versus 30%, 9/30). Conclusions Urinary tract infection is common in dogs with TCC highlighting the importance of regular monitoring for bacterial cystitis in dogs with TCC. In addition, clinical factors such as tumor location and sex may be predictive of positive culture and can help clinicians assess the risk of UTI.